6755 Improving confidence in neonatal management through effective in-situ simulation teaching - Elliott, Jonathan; Penumala, Viswavani (Archives of disease in childhood, 2024)
ObjectivesWe set out to improve an existing in-situ neonatal simulation programme in a District General Hospital setting. The paediatric department had a weekly 30 minute slot dedicated to Registrar facilitated neonatal simulation, with the content of sessions determined by the facilitator on the day. These sessions were understood to be poorly attended, often didn’t occur and the educational value was largely unknown due to the lack of formalised curriculum.MethodsTo gauge opinion on the existing programme we sent an anonymised survey to the junior doctor cohort in the paediatric department, this also served to identify reasons for sessions not going ahead and attendance. Using the information collected we then produced a new simulation programme, developing a new curriculum of simulation scenarios with defined learning objectives, designed to be used by a facilitator who may not be simulation trained (including potential discussion points for debriefing). On introducing this new curriculum, we sent the scenario to the assigned facilitator in advance of the session. We also moved the sessions to a time when a consultant could be present to help the facilitator, or to take over if the facilitator is called away. We then gained feedback from these sessions over the following 3 months using another anonymised survey, focussing on participant’s perception of the sessions usefulness to their training (scored out of 5), and how it could be improved.ResultsPrior to introducing the new curriculum, the weekly sessions were only going ahead 60% of the time. Our initial survey revealed that this was primarily due to workload and timing of the sessions. In the 3 months after the changes were implemented, the weekly sessions occurred on 100% of the available weeks. Participants perceptions of the sessions improved, with their ratings increasing from an average of 3.8/5 prior to the new curriculum being introduced, to 4.7/5 after its introduction. Multiple participants commented on how these sessions had increased their confidence in neonatal resuscitation and management, as well as mentioning how productive the debrief and discussion after had been.ConclusionIntroducing a set and defined curriculum of simulation scenarios for a neonatal in-situ simulation programme has shown an improvement in the sessions usefulness for junior doctor’s training, as well as improving confidence in neonatal management within the cohort. We have also shown that by determining and addressing the factors causing teaching sessions not to go ahead, we can improve their occurrence and attendance.